2013
DOI: 10.1007/s12028-013-9936-9
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculostomy-Associated Infection: A New, Standardized Reporting Definition and Institutional Experience

Abstract: Our standardized VAI definition and CDC format seems promising toward facilitating future study and guideline development. Given our strict protocol of sterile catheter placement and care, and our institution's low 2.0% infection rates, we propose an infection-rate target of ≤5 per 1,000 device days. Our results suggest that the use of antibiotics or antibiotic-impregnated catheters is unwarranted--a positive given concerns of evolving anti-microbial resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The defined time at which a positive CSF culture first qualified as a VRI varied from any time after catheter insertion 9 to 24 11,16 to 48 4 hours after placement. The timeframe at which VRI is diagnosed after EVD removal also varied from three days 12 to four weeks 25 after EVD removal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The defined time at which a positive CSF culture first qualified as a VRI varied from any time after catheter insertion 9 to 24 11,16 to 48 4 hours after placement. The timeframe at which VRI is diagnosed after EVD removal also varied from three days 12 to four weeks 25 after EVD removal.…”
Section: Resultsmentioning
confidence: 99%
“…While some used vague terms such as “clinical picture” 13 or “clinical signs” 18,23 of infection, others used a quantitative scale 18,19 , or specified individual clinical signs and symptoms including cranial nerve signs, headache 25 , photophobia, seizures 15,21 , stiff neck 21,25 , altered mental status 9,15,21 , irritability 9,25 , inflammation at the catheter site 9 , and fever. In some cases fever was undefined 15,18,19,21 , and in others it was defined as 38 25 , 38.5 10 , and 38.6 degrees Celsius 12 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 To further illustrate the variability in defining VAIs, one study applied criteria from Honda et al, Gozal et al, and Citerio et al to a retrospective series and found that rates of infection based on each authors' criteria were 60%, 56%, and 23%, respectively. 11,25,30,51 In 2014, Gozal et al proposed a standardized definition of VAIs as a positive CSF culture in a patient with a ventriculostomy catheter and one of the following: a fever > 101.5°F, a CSF glucose level < 50 mg/dl, or a CSF glucose level < 50% of any serum glucose drawn within 24 hours of CSF sample. 25 Most recently, the 2017 Infectious Diseases Society of America guidelines on healthcare-associated ventriculitis and meningitis did not give a definition of VAI, but provided guidance for when clinical suspicion prompts CSF sampling for infection.…”
Section: Complications Of Invasive Intracranial Pressure Monitoring Dmentioning
confidence: 99%
“…11,25,30,51 In 2014, Gozal et al proposed a standardized definition of VAIs as a positive CSF culture in a patient with a ventriculostomy catheter and one of the following: a fever > 101.5°F, a CSF glucose level < 50 mg/dl, or a CSF glucose level < 50% of any serum glucose drawn within 24 hours of CSF sample. 25 Most recently, the 2017 Infectious Diseases Society of America guidelines on healthcare-associated ventriculitis and meningitis did not give a definition of VAI, but provided guidance for when clinical suspicion prompts CSF sampling for infection. CSF pleocytosis with a positive culture and infectious symptoms are indicative of VAI, a strong recommendation with a high level of evidence.…”
Section: Complications Of Invasive Intracranial Pressure Monitoring Dmentioning
confidence: 99%